The role of social support in the association between quality of life and demoralization in patients with inflammatory bowel disease: a cross-sectional study - Ji, Jingrui; Gu, Haoran; Lei, Sifei; Shen, Pan; Zheng, Jie; Zhang, Yinling (Frontiers in Psychology, 2025)
PurposeThis study aims to investigate the associations among social support, quality of life, and demoralization in patients with inflammatory bowel disease (IBD), and to test the hypothesized mediating role of social support between quality of life and demoralization.MethodsA cross-sectional study was conducted using a convenience sampling approach. A total of 293 patients with inflammatory bowel disease (IBD) were recruited from the gastroenterology departments of three tertiary-level hospitals in Xi’an, China, between January and July 2024. Data were collected using a general information questionnaire, the Chinese version of the Demoralization Scale-II (DS-II), the Social Support Rating Scale (SSRS), and the Inflammatory Bowel Disease Questionnaire (IBDQ). Internal consistency reliabilities (Cronbach’s α) were 0.801, 0.825, and 0.986 for the DS-II, SSRS, and IBDQ, respectively. Correlation analyses and structural equation modeling (SEM) with bootstrapping (5,000 resamples, bias-corrected) were used to examine relationships and test mediation.ResultsSocial support was positively correlated with quality of life (r = 0.171, 95% CI [0.052, 0.285], p < 0.01), and negatively correlated with demoralization (r = −0.402, 95% CI [−0.499, −0.295], p < 0.01). Quality of life was negatively correlated with demoralization (r = −0.490, 95% CI [−0.575, −0.395], p < 0.01). Social support partially mediated the relationship between quality of life and demoralization, accounting for 22.12% of the total effect (indirect effect = −0.125, 95% CI [−0.178, −0.082]).ConclusionSocial support plays a significant partial mediating role in the relationship between quality of life and demoralization in IBD patients. These cross-sectional findings suggest that interventions aimed at enhancing social support may help mitigate demoralization and improve quality of life, though longitudinal or experimental studies are needed to confirm causal pathways.